Advanced nutrition and human metabolism - Gropper, Sareen Annora Stepnick; Smith, Jack L. (Wadsworth/Cengage Learning, 2013)
Covers the biochemistry of vitamins, minerals, and energy nutrients. This title examines the structure and function of water-soluble and fat-soluble vitamins and their regulatory role in metabolism, looks at electrolyte and fluid balance, and covers the role of nutrition in the development or exacerbation of chronic disease